DETERMINANTS OF STUNTING IN SEMARANG CITY - Roro Kushartanti (Homes Journal = Hospital Management Studies Journal, 2023)
Background : Stunting is not only a problem of physical growth disorders, but also causes children to become sick easily, brain and intelligence development also occurs. So, stunting is a big threat to the quality of human resources in Indonesia. The purpose of writing of this literature review is to collect determinants of Stunting in Semarang. Objective : This research uses a literature revies from Google Scholar library sources, which is presented descriptively according to the problem formulation. Result : Review from some of articles, found that maternal education level, maternal occupation, child order, birth length, child rearing patterns, exclusive breastfeeding status, family income, housing conditions, nutritional intake, and history of KEK are risk factors determining the incidence of Stunting in the Semarang. Conclusions : Stunting prevention programs must be improved, by screening and monitoring the growth and development of babies and toddlers to prevent Stunting from an early age. Public is also advised to be more diligent in carrying out examinations at health services to monitor children’s growth and development.